Effects of Clinacanthus nutans and Aloe vera Extracts on bFGF Synthesis in Fibroblasts - Rezky Anggraeni; Moehamad Orliando Roeslan (Indonesian Dental Association, 2022)
Introduction: Wound healing is an important but complicated process, containing a multifaceted process. The growth factor involved in the wound healing process is basic fibroblast growth factor (bFGF). Clinacanthus nutans (C. nutans) and A. vera are traditional plants that have the ability to induce fibroblast migration. However, no study has yet compared the effects of C. nutans and A. vera on bFGF protein synthesis associated with wound healing. Objective: The aim of this study was to evaluate the effect of extracts of C. nutans and A. vera on the fibroblast synthesis of bFGF in fibroblasts. Method: Clinacanthus nutans leaf powder was extracted using a solution of hexane and chloroform sequentially. While the A. vera gel is taken. Fibroblasts were treated with several concentrations (10, 50, and 100 µg/mL) within 24 hours. Synthesis of bFGF protein was tested using enzyme linked immunoabsorbent assay (ELISA). Result: The chloroform extract of C. nutans and A. vera up regulated the synthesis of bFGF. Concentration of 10 µg/mL C. nutans showed the highest bFGF protein synthesis compared to other treatment groups. Conclusion: Chloroform extract of C. nutans and A. vera can up regulated the synthesis of bFGF in fibroblasts. ABSTRAK Pendahuluan: Penyembuhan luka adalah proses penting namun rumit, yang terdiri dari beberapa fase penyembuhan. Faktor pertumbuhan yang berhubungan dengan proses penyembuhan luka adalah, basic fibroblast growth factor (bFGF). Clinacanthus nutans (C. nutans) dan Aloe vera (A. vera) adalah tumbuhan tradisional yang memiliki kemampuan untuk menginduksi migrasi fibroblas. Namun, belum ada penelitian yang telah membandingkan efek C. nutans dan A. vera terhadap sintesis protein bFGF yang berhubungan dengan luka penyembuhan. Tujuan: Tujuan dari penelitian ini adalah untuk mengetahui efek ekstrak C. nutans dan A. vera terhadap sintesis bFGF pada fibroblas. Metode: Bubuk daun C. nutans di ektraksi menggunakan larutan heksana dan kloroform secara berurutan. Sedangkan A. vera diambil gel nya. Fibroblas diberi perlakuan dengan beberapa konsentrasi (10, 50, dan 100 µg/mL) dalam waktu 24 jam. Sintesis protein bFGF diuji menggunakan enzym linked immunoabsorbent assay (ELISA). Hasil: Ekstrak kloroform C. nutans dan A. vera dapat meningkatkan sintesis protein bFGF lebih tinggi dibandingkan dengan kontrol negatif pada uji ELISA. C. nutans konsentrasi 10 µg/mL menunjukkan sintesis protein bFGF tertinggi dibandingkan dengan kelompok perlakuan lain. Kesimpulan: Ekstrak kloroform C. nutans dan A. vera dapat meningkatkan sintesis protein bFGF pada fibroblas.